Trust the Process: A New Scientific Outlook on Psychodramatic Spontaneity Training - Yaniv, Dani (Frontiers in Psychology, 2018)
Human mind is hypothesis-driven and our observations of the world are strongly shaped by preconceptions. This "top-down" principle is biologically driven and contraindicative to spontaneity, which is non-linear, condensed and initially incomprehensible. My first argument is that spontaneity entails "bottom up" information processing, as articulated in the hierarchical neurocognitive model of perception. My second argument is that changing the balance between these two processes is important and feasible. Insights from psychodynamic transference and savant syndrome are presented to support these ideas. Uniting these contemporary notions with some essentials of J.L. Moreno’s philosophy is my third goal. By violating predictions and expectations, psychodrama interferes with top-down “conserved” processing and cultivates here and now, stimulus-dependent spontaneous acts. Further evidence is presented in support of the claim that adult spontaneity leads to enhanced cognition and creativity through imitating the child’s brain, as Moreno envisioned. Because spontaneity is formed before having the evidence for its truth or adequacy, it entails, in adults, overcoming apprehensions about acting without a theory in mind. This is what trusting-the-process means and it requires training, which psychodrama fosters on its stage laboratory.